Optimal monetary policy rules for the euro area: an analysis using the area wide model - Alistair Dieppe; Keith Kuester; Peter McAdam (European Central Bank (ECB), 2004)
In this paper, we analyze optimal monetary policy rules in a model of the euro area, namely the ECB's Area Wide Model, which embodies a high degree of intrinsic persistence and a limited role for forward-looking expectations. These features allow us, in large measure, to differentiate our results from many of those prevailing in New Keynesian paradigm models. Speci?cally, our exercises involve analyzing the performance of various generalized Taylor rules both from the literature and optimized to the reference model. Given the features of our modelling framework, we ?nd that optimal policy smoothing need only be relatively mild. Furthermore, there is substantial gain from implementing forecast-based as opposed to outcome-based policies with the optimal forecast horizon for in?ation ranging between two and three years. Benchmarking against fully optimal policies, we further highlight that the gain of additional states in the rule may compensate for a reduction of communicability. Thus, the paper contributes to the debate on optimal monetary policy in the euro area, as well as to the conduct of monetary policy in face of substantial persistence in the transmission mechanism.
Keywords: E4; E5; 330; euro area; monetary policy rule; optimization